Identifikasi Kebutuhan Peserta Didik di Sekolah-Sekolah Kabupaten Flores Timur Desa Pledo - Rohi, Enasely Mega Wenyi; Margaretha, Dhiu (Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2023)
Student service camp activities are a form of community service in disseminating Student Needs Questionnaires (AKDP) in schools and taking a role in providing information services for students at school. Implementing AKDP in schools aims to know every dominant problem in several schools spread across Pledo Village, Witihama District, and East Flores Regency. The results of the spread of AKPD in several schools can provide benefits. The benefit of this activity is that schools know what problems are experienced by students related to four areas of service, namely, the fields of personal, social, learning and career services and can help BK teachers develop programs related to the problems of each school.